2022
DOI: 10.1007/s11356-022-22130-9
|View full text |Cite
|
Sign up to set email alerts
|

Complementarity of two approaches based on the use of high-resolution mass spectrometry for the determination of multi-class antibiotics in water. Photodegradation studies and non-target screenings

Abstract: The development of analytical methodologies to monitor different antibiotic families in water and the implementation of alternatives for their efficient elimination are a great challenge. The aim of this research was to develop a method based on solid-phase extraction followed by ultra-high performance liquid chromatography coupled to quadrupole time-of-flight mass spectrometry to analyse multi-class antibiotics, including macrolides, cephalosporins, fluoroquinolones, sulfonamides and diaminopyrimidines, in wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…The use of NTS in advanced oxidation processes (AOPs) is on the rise. It offers several advantages, including the identification of unknown transformation products (TPs), understanding how the water matrix influences the formation of new TPs, determining treatment efficiency on a global scale, detecting abnormalities early, optimizing processes, and making decisions [5,53]. Furthermore, it was found that AOP treatment evaluation can be improved by adding supercritical fluid chromatography (SFC)-HRMS to the LC-HRMS-based workflow for identifying unknown persistent and mobile organic compounds (PMOCs) found in groundwater samples to achieve greater detection coverage of highly polar compounds [54].…”
Section: Selected Nts Approaches In Water Analysis Studiesmentioning
confidence: 99%
“…The use of NTS in advanced oxidation processes (AOPs) is on the rise. It offers several advantages, including the identification of unknown transformation products (TPs), understanding how the water matrix influences the formation of new TPs, determining treatment efficiency on a global scale, detecting abnormalities early, optimizing processes, and making decisions [5,53]. Furthermore, it was found that AOP treatment evaluation can be improved by adding supercritical fluid chromatography (SFC)-HRMS to the LC-HRMS-based workflow for identifying unknown persistent and mobile organic compounds (PMOCs) found in groundwater samples to achieve greater detection coverage of highly polar compounds [54].…”
Section: Selected Nts Approaches In Water Analysis Studiesmentioning
confidence: 99%
“…Additionally, higher extraction recoveries and lower matrix effects were reported when compared to traditional SPE, as it removes the species responsible for such matrix effects. 42 According to previously reported methods, 43,44 methanol was the appropriate solvent for the elution of those drugs, but in accordance with green analytical chemistry, various water ratios were added to methanol. The ratio of water: methanol (20 : 80, v/v) nearly showed similar results as 100% methanol elution solvent.…”
Section: Sample Preconcentration and Extractionmentioning
confidence: 99%